2021
DOI: 10.3389/fpsyg.2021.642992
|View full text |Cite
|
Sign up to set email alerts
|

Developing Resilience During the COVID-19 Pandemic: Yoga and Mindfulness for the Well-Being of Student Musicians in Spain

Abstract: Here, we report on a quasi-experimental study to explore the applicability and perceived benefits of the CRAFT program, which is based on mindfulness, yoga, positive psychology, and emotional intelligence, to improve higher education student musicians’ health and well-being during the lockdown. A subset of student musicians at a Higher Conservatory of Music in Spain followed the CRAFT program during the academic year 2019/2020, 1 h per week as part of their curriculum. Students enrolled in CRAFT-based elective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
1
29
0
4
Order By: Relevance
“…Emotional intelligence is a protective factor of well-being ( Hussien et al, 2020 ; Bermejo-Martins et al, 2021 ; Moroń and Biolik-Moroń, 2021 ), and directly and indirectly contributes to improving psychoeducational variables in university students ( Iqbal et al, 2021 ). It has aided in the development of resilience, well-being, and mental health in Spanish students during the COVID-19 pandemic ( Bartos et al, 2021 ). Specifically, emotional intelligence is a predictor of psychological well-being, enabling healthier coping strategies during COVID-19 pandemic by avoiding emotional distress ( Sánchez-Ruiz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional intelligence is a protective factor of well-being ( Hussien et al, 2020 ; Bermejo-Martins et al, 2021 ; Moroń and Biolik-Moroń, 2021 ), and directly and indirectly contributes to improving psychoeducational variables in university students ( Iqbal et al, 2021 ). It has aided in the development of resilience, well-being, and mental health in Spanish students during the COVID-19 pandemic ( Bartos et al, 2021 ). Specifically, emotional intelligence is a predictor of psychological well-being, enabling healthier coping strategies during COVID-19 pandemic by avoiding emotional distress ( Sánchez-Ruiz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we focused on examining through qualitative methods the responses provided by proactive CRAFT participants to an open-ended question in an online questionnaire (Bartos et al, 2021). This question asked which particular practice or practices participants had implemented, where they learned it, and briefly describe their own experience with it and the impact they had on their physical, mental, and emotional state.…”
Section: Discussionmentioning
confidence: 99%
“…Against this backdrop, a porous movement of seekers of supirichuaru kea (spiritual care)-also referred to as kokoro no kea (care of mind) by the media and health and religious professionals-has developed, composed of individuals who do not source only from conventional forms of collective rituals and popular religious-cultural activities for their emotional relief. Studies have shown that spiritual practices for self-care such as meditation, relaxation, and mind-body disciplines have been positively correlated with increased selfresilience during the pandemic (Lucchetti et al 2020;Bartos et al 2021;Sahni et al 2021) in that individuals develop necessary resources-such as psychological and emotional resources-to self-regulate their behaviour and successfully adapt to stressful circumstances (Koenig 2008;Hart and Koenig 2020). Findings have already revealed the effectiveness of such self-resilience among the Japanese during the COVID-19 pandemic (Kubo et al 2021;Sugawara et al 2020).…”
Section: "Kokoro No Kea" During the Pandemic: Institutional Responsesmentioning
confidence: 99%